Making judges independent: some proposals regarding the judiciary - Lars P. Feld; Stefan Voigt (Philipps-Universität Marburg, Fachbereich Wirtschaftswissenschaften, 2004)
It is argued that an independent judiciary is a necessary condition for both individual liberty and economic prosperity. After having surveyed the literature dealing with how to arrange for an independent judiciary, the authors derive some additional policy implications by drawing on two indicators of judicial independence (JI) recently introduced by them. De facto JI has a robust and highly significant impact on economic growth. Individual components of both de jure and de facto JI on economic growth are estimated for their impact on economic growth. Additionally, the effects of other institutional arrangements such as presidential vs. parliamentary systems are inquired into.
Keywords: H11; K40; P51; 330; Judicial Independence; Constitutional design; Positive Constitutional Economics; Economic Growth; Justiz; Selbstverwaltung; Verfassung; Wirtschaftswachstum; Schätzung; Welt